Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.cgd.5b01695
|View full text |Cite
|
Sign up to set email alerts
|

Searching New Crystalline Substrates for OMBE: Topological and Energetic Aspects of Cleavable Organic Crystals

Abstract: Thin films of organic semiconductors are intensively studied in view of their exploitation in modern electronic devices. Until now, few crystalline substrates have been used as clean surfaces for organic molecular beam epitaxy (OMBE). Among them, β-alanine crystals recently proved to be valuable substrates because of their cleavage along (010) surfaces. To increase the set of available substrates, we searched layered structures through the Cambridge Structural Database by means of the ToposPro program package.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 64 publications
(111 reference statements)
0
27
0
Order By: Relevance
“…Microscopic models of the mechanical deformation, including not only bendable and brittle types, but also shearing (Bag et al, 2012;Ghosh & Reddy, 2012;Krishna, Shi et al, 2015) and twisting (Saha & Desiraju, 2017a,b;Gupta et al, 2018) were suggested. The simple model that was used to describe plastic bending of organic crystals on external stress (Reddy et al, 2005) was applied to more than 20 other systems (Reddy et al, 2006;Baudron, 2010;Ghosh & Reddy, 2012;Krishna, Devarapalli et al, 2015;Krishna, Shi et al, 2015;Panda et al, 2015;Plotnikov & Martinez, 2016;Zolotarev et al, 2016). Local perturbations in plastically bent crystals can be monitored experimentally (Panda et al, 2015;Pejov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic models of the mechanical deformation, including not only bendable and brittle types, but also shearing (Bag et al, 2012;Ghosh & Reddy, 2012;Krishna, Shi et al, 2015) and twisting (Saha & Desiraju, 2017a,b;Gupta et al, 2018) were suggested. The simple model that was used to describe plastic bending of organic crystals on external stress (Reddy et al, 2005) was applied to more than 20 other systems (Reddy et al, 2006;Baudron, 2010;Ghosh & Reddy, 2012;Krishna, Devarapalli et al, 2015;Krishna, Shi et al, 2015;Panda et al, 2015;Plotnikov & Martinez, 2016;Zolotarev et al, 2016). Local perturbations in plastically bent crystals can be monitored experimentally (Panda et al, 2015;Pejov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Students in Milano -Bicocca are prompted to assess the possible presence of cleavage in their structures due to the relevance of this property in low-dimensional materials. A computational approach based on a topological analysis of crystal structures supported by energy evaluation has been demonstrated to be robust enough to extract 2D hydrogen-bond networks giving rise to perfect cleavage in a specific class of organic crystals (Zolotarev et al, 2016). Unfortunately, a random check of the scientific literature pertinent to the 134 hexaaqua systems described here revealed no discussion of this fundamental property.…”
Section: Description Of the Selected Crystal Structuresmentioning
confidence: 95%
“…Flat naphthalene diimine derivatives were found to have comparable crystal packing governed by π...π stacking, similar crystal morphology, but exhibited various mechanical flexibility attributed to close packing or interlock of their terminal alkyl chains [177]. Investigation of sulfa drug crystals [178], co-crystals of vanillin isomers [179], and amino acids [180] demonstrated that H-bonded layered structures with orthogonal distribution of strong and weak interactions attain the feasibility of cleaving a crystal along a given crystallographic plane parallel with these robust synthons.Particularly, single crystals with molecular surfaces formed by hydrophobic interactions can be applied as clean surfaces for molecular beam epitaxy. The presence of slip planes is also thought to be associated with low elastic recovery upon compression, and greater plasticity [181,182].…”
Section: Bfdh Morphology Predictionmentioning
confidence: 99%